The monetary presentation of the euro area balance of payments - Louis Bê Duc; Frank Mayerlen; Pierre Sola (European Central Bank (ECB), 2008)
This occasional paper describes the monetary presentation of the euro area balance of payments and its use. The monetary presentation is a tool for assessing the impact of balance of payments transactions involving non-bank residents on monetary developments. The paper explains in detail the principle underlying this approach, i.e. the link between the external counterpart of money, as reflected in the balance sheet of the banking sector, and the balance of payments. From a statistical perspective, it is shown that the monetary presentation of the balance of payments, which is based on international statistical standards, may be applied in any country or currency union. With regard to euro area statistics, the paper elaborates on the practical implementation of the monetary presentation, while also describing a few approximations and remaining statistical challenges. Finally, the paper assesses how the monetary presentation of the balance of payments has been used for analysing monetary developments in the euro area, and highlights the significant impact of balance of payments transactions on monetary dynamics in certain periods.
Keywords: E51; F40; 330; Monetary analysis; capital flows; balance of payments; Zahlungsbilanz; Kapitalmobilität; Eurozone; EU-Staaten